Exacerbation of Hyperparathyroidism, Secondary to a Reduction in Kidney Function, in Individuals With Vitamin D Deficiency - Daimon, Makoto; Fujita, Tomoyuki; Murabayashi, Masaya; Mizushiri, Satoru; Murakami, Hiroshi; Nishiya, Yuki; Tanabe, Jutaro; Matsuhashi, Yuki; Yanagimachi, Miyuki; Tokuda, Itoyo; Sawada, Kaori; Ihara, Kazushige (Frontiers in Medicine, 2020)
Aims/Introduction: Chronic kidney disease (CKD)-mineral and bone disorders (CKD-MBD) are an adverse outcome derived from decreases in kidney function, where abnormality of serum concentrations of calcium (Ca), parathyroid hormone (PTH), and vitamin D can be seen coordinately. To identify individuals at risk for CKD-MBD or secondary hyperparathyroidism, the relationships between estimated glomerular filtration rate (eGFR) and serum PTH concentration were evaluated, allowing for confounding factors, in particular vitamin D status, in a general Japanese population. Materials and Methods: Nine-hundred-and-thirty participants in the population-based Iwaki study conducted in 2016 who were not on drugs affecting Ca metabolism nor hemodialysis, were included in the study (326 men and 604 women; age: 55.4 ± 15.9 years). Results: Regression analysis showed a significant correlation between eGFR and serum intact PTH concentration, after adjustment for possible confounding factors (β=−0.122, p<0.001). The smoothed spline curve applied for the correlation analysis revealed a biphasic correlation, with a division at an eGFR of ~60 mL/min/1.73m², below which the correlation coefficient was higher (β=−0.405, p<0.001). Stratification on the basis of vitamin D status showed that the correlation was present only in participants with vitamin D deficiency (25-dihydroxyvitamin D3: <15 pg/mL) (β=−0.154, p<0.001). Conclusions: These results indicate that a reduction in eGFR is a significant risk factor for an increase in serum PTH concentration when it is <60 mL/min/1.73m² and vitamin D is deficient, in the general Japanese population.